Subcontractor selection method using analytic hierarchy process - Manoharan, Ravichandran (2005)
Sub-contractor selection is one of the most important aspects in construction contract. The success level of construction is very depends on the quality of subcontractor selection process. Majority of selection process are over emphasized on the bid cost rather than trade-off between other parameter such as quality, safety and environmental commitments. Instead these have contributes in project delays, cost overruns, non-confirmation on quality, lost time accident, increase number of claims, litigation and contractual issues and failure to comply with local authority and construction specification. Concerning to this problems, the subcontractor prequalification, evaluation and selection process needs to be reviewed to achieve the project goals based on multi criteria decision making process. The main initial thrust of this study was to identify the criteria used for selection process, which was adopted by the various type of contractor working in Putrajaya. This exercise involved â€œknowledge acquisitionâ€ phase to capture the expert knowledge including collecting documents of current procurements practice, knowledge from the literature review and interviews with experts from various construction companies. The data collected are used to create a theoretical model for subcontractor selection that represented by the Analytic Hierarchy Process. It is concludes that the choice of subcontractor should be consider based on multi criteria decision rather than automatically accepting the lowest bid. The finding from the research indicated that the common criteria considered by the contractor during the selection are the cost, past performance, financial soundness, technical expertise, management capability, subcontractor workload, previous work experience, and track record. The study recommended that procurers should no longer depends totally on their experience to decide on their selection process but an effective decision support system (DSS) like Analytic Hierarchy Process (AHP) is important to systematically evaluate the selection process. The research also serves as sources of information for subcontractor to win the contract and act as platform for contractor to make an appropriate decision on the choice of subcontractor